2014
DOI: 10.3390/ijerph110707425
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight/Obesity and Its Associated Factors among University Students from 22 Countries

Abstract: Obesity among young people increases lifetime cardiovascular risk. This study assesses the prevalence of overweight/obesity and its associated factors among a random sample of university students from 22 universities in 22 low, middle income and emerging economy countries. This cross-sectional survey comprised of a self-administered questionnaire and collected anthropometric measurements. The study population was 6773 (43.2%) males and 8913 (56.8%) females, aged 16 to 30 years (mean 20.8 years, SD = 2.6). Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
184
13
34

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(272 citation statements)
references
References 33 publications
41
184
13
34
Order By: Relevance
“…1. The majority of participants were females (~60%), in agreement with previous studies, which reported higher prevalence of overweight and obesity in female university students [19] . An effect of individual counselling was superior to group counselling for weight loss and BMI.…”
Section: Resultssupporting
confidence: 79%
“…1. The majority of participants were females (~60%), in agreement with previous studies, which reported higher prevalence of overweight and obesity in female university students [19] . An effect of individual counselling was superior to group counselling for weight loss and BMI.…”
Section: Resultssupporting
confidence: 79%
“…Regarding excess body weight, in general, it could be observed that its occurrence was similar to those found in university students in other countries 27 and in Brazil 4 . The results indicate that excess body weight was more prevalent in men, coinciding with the findings from certain studies; however, this diverges from other studies that show similarities between both sexes.…”
Section: Discussionmentioning
confidence: 60%
“…5 Similarly, many studies have been conducted worldwide emphasising the unhealthy behaviour and lifestyles of university students. [6][7][8][9][10][11][12][13][14][15][16] Behaviours and lifestyle habits formed during the university years are likely to be continued throughout adulthood and could contribute to increased development of noncommunicable diseases (NCDs), namely diabetes, cardiovascular disease (CVD), coronary heart disease (CHD) and cancers. 14,17,18 Multiple factors can influence student wellness, such as limited or expensive food choices, time constraints, psychological issues, substance abuse and a sedentary lifestyle.…”
Section: Introductionmentioning
confidence: 99%